El Coliseo del Buen Retiro. Una hipótesis arquitectónica a partir del levantamiento de René Carlier de 1712 - Juan Ruesga Navarro; Vicente Palacios Galán (Mélanges de la Casa de Velázquez)
The purpose of this article is to formalise a hypothesis concerning the Coliseum of the Buen Retiro and to express it by means of a virtual reconstruction of the theatre itself in order to explain the functioning of the hall and its relationship with the Palace. This hypothesis is based on the survey carried out in 1712 by the architect René Carlier, preserved in the Bibliothèque Nationale de France, and other documents. The Coliseo del Buen Retiro (1640) was the first theatre in Spain to be equipped with Italian-style stage machinery, thanks to the collaboration between the architect Alonso Carbonell and the set designer Cosme Lotti. It formed part of the buildings of the Buen Retiro Palace in Madrid, built during the reign of Philip IV, where important texts by Pedro Calderón de la Barca were performed and constitutes an essential piece in the history of Spanish theatre.